Evaluasi Kualitas Layanan dalam E-Commerce: Studi Kasus pada Platform Shopee - Rayhan Arief Widitya; Mohamad Rafi; Adinda Faniyah Yusha (Journal of Management and Creative Business, 2024)
This study aims to assess the quality of services in e-commerce, focusing on online shopping platforms, particularly Shopee. High-quality service is expected to enhance customer satisfaction and loyalty, which in turn plays a vital role in the success of businesses in the e-commerce sector. With rising competition among online shopping platforms, superior service quality becomes a key factor in attracting and retaining customers. This research utilizes the E-SERVQUAL method to evaluate various dimensions of service quality, such as efficiency, fulfillment, and responsiveness, to pinpoint areas in need of improvement. The study's findings reveal a considerable gap between customer expectations and the actual services perceived on Shopee's platform. The dimensions of service efficiency and responsiveness were identified as the weakest, where customers noted that the transaction process was often slow, and complaints were not promptly addressed. These results highlight the need for service quality enhancements to meet customer expectations and foster greater user satisfaction and loyalty. This research is anticipated to offer valuable insights for Shopee's management in devising more targeted strategies to improve service quality. Overall, the study contributes significantly to the development of service policies in the e-commerce industry, particularly for platforms looking to strengthen their competitive edge in an increasingly competitive market.